What a weight loss programme should contain if people with obesity were asked - a qualitative analysis within the DO:IT study - Christina Jessen-Winge; Pia Maria Ilvig; Heather Fritz; Carl J. Brandt; Kim Lee; Jeanette Reffstrup Christensen (BMC, 2021)
Abstract Background Currently 1.9 billion adults worldwide are estimated to be overweight or obese. In Denmark the municipalities hold the responsibility to deliver weight loss programmes to overweight and obese citizens. There is a tendency to assume that weight loss programmes that show positive effects in specialized hospital settings are directly transferrable to municipal settings. However, municipality-based weight loss programmes have not produced clinically significant reductions in body weight. One reason for this may be that much research evidence regarding obesity programming neglects the perspectives of people with obesity. The first step in developing a weight loss programme designed for municipal settings is to understand what people with obesity want and need from a programme. The aim of this study was to examine what people with obesity find important in a weight loss programme for weight loss and weight maintenance. Methods We used a qualitative, explorative, descriptive design with individual interviews. We included men and women age 17 and older with a BMI ≥ 25 kg/m2. Participants were recruited from the wait lists of 13 municipality programmes and through Facebook posts. Data were analyzed using content analysis. Results Thirty-four participants with overweight or obesity were individually interviewed (ages between 19 and 74). Findings suggest that weight loss programmes should; a) support participants in structuring days; b) consider the use of replacement activities to reduce cognitive and emotional burden; c) aide individuals to increase self-efficacy and; d) include family and friends as well as health professionals and peers in the weight loss process. Diet and exercise, while important, should be balanced with other meaningful activities in everyday life. Conclusion Participants in this study wished to balance weight loss related activities with overall everyday life as well as finding the believe in their ability to lose weight in social relations.